Philosophy of mental representation - Clapin, Hugh (Oxford University Press, 2002)
In Philosophy of Mental Representation five of the most original and important thinkers in philosophy of mind engage in an overlapping dialogue about mental representation. In new papers, contributors Andy Clark, Robert Cummins, Daniel Dennett, John Haugeland and Brian Cantwell Smith each investigate the views and claims of one of the other contributors regarding mental representation. The subject then offers a reply. An exciting feature of this collection is the dynamic discussion among all contributors following each exchange. This collection offers the latest thinking on mental representation carefully and critically analysed by the leading thinkers in the field.